Increased cortisol levels caused by acute resistance physical exercise impair memory and learning ability - Bermejo, José L; Valldecabres, Raul; Villarrasa-Sapiña, Israel; Monfort-Torres, Gonzalo; Marco-Ahulló, Adrià; Ribeiro do Couto, Bruno (PEERJ, 2022)
Acute physical exercise works as an activator of the responses of the human organism to stress. This is based on the activation of the hypothalamic-pituitary-adrenal (HPA) axis, affecting physical, physiological and psychological levels. This study aimed to analyse the effects of a single bout of high-intensity resistance exercise on cognitive-behavioural responses: visuo-spatial path learning and memory, as well as physiological responses (salivary cortisol levels). Nineteen healthy male militarytrained powerlifting subjects were tested in a within-subject design on two experimental days with an interval of 48 h. The stress and cognitive variables were measured by cortisol levels and Ruff-Light trail-learning test (RULIT) test scores, respectively. The results showed the immediate influence of acute exercise on cortisol, with significantly higher cortisol levels found in subjects after completion of the acute resistance exercise. In addition, this study found a significant deterioration of memory and learning ability after a dose of intense resistance exercise. In conclusion, the study highlights the relative effects of resistance exercise on cortisol and cognitive performance depending on the intensity and type of the exercise, the moment of measurement and the cerebral areas implicated.
Keywords: acute exercise; cortisol; cognitive performance; memory; learning; JCR; Scopus